The Use of Duolingo Application for English Vocabulary Learning in 11th Grade Students of MA Quraniyah Batu Kuta Narmada - Gifari, Dimas Rizaldi Al; Melani, Boniesta Zulandha; Suryaningsih, Hartati; Amin, Muhammad (LITPAM, 2026)
Students in Islamic boarding schools often face limited access to digital devices and technology-based learning tools, which can hinder their English vocabulary development, particularly in productive vocabulary. In addition, many students struggle to use vocabulary actively in translation and sentence construction due to monotonous learning methods. This study examines the use of the Duolingo application for English vocabulary learning in 11th-grade students of MA Quraniyah Batu Kuta Narmada. The study aimed to determine whether there was a significant difference in students' vocabulary learning before and after using Duolingo as a supplementary learning tool. The research also addressed the limited studies concerning the implementation of technology-based learning applications in boarding school environments with restricted access to digital devices. This study employed a pre-experimental research design using a one-group pre-test and post-test design. The participants consisted of 20 students selected through a total sampling technique. The data were collected through vocabulary pre-test and post-test consisting of multiple-choice, matching picture, translation, and fill-in-the-blank items. The treatment was conducted in four meetings over one week using Duolingo materials related to Fitness, Travelling, Theme Park, and Medicine. The data were analyzed using descriptive statistics, the Shapiro-Wilk test, and the Wilcoxon Signed Ranks Test. The findings revealed that students' vocabulary learning improved significantly after the implementation of Duolingo. The mean score increased from 57.25 in the pre-test to 79.25 in the post-test. The results of the Wilcoxon Signed Ranks Test showed a Z value of -3.942 with an Asymp. Sig. (2-tailed) value of less than 0.001, confirming a statistically significant difference between pre-test and post-test scores. Furthermore, students showed improvement in both receptive and productive vocabulary. The study concludes that Duolingo can effectively support vocabulary learning in technology-limited boarding school environments through supervised classroom implementation.